POTRET WAJAH SOSIAL POLITIK INDONESIA DALAM PUISI GUS MUS “NEGERI HAHA HIHI” - Yheshinta Nabilla Navayanesty D.T; Rima Listiawati; Titik Sudiatmi (Jurnal Bastra (Bahasa dan Sastra), 2025)
The author criticizes through literary works during the New Order period which was one of the downtrodden periods of the Indonesian people. The existence of the poem "The Land of Haha Hihi" by K.H Mustofa Bisri or known as Gus Mus was written as a form of resistance because the rights as the people were taken away and the people continued to experience oppression. The poem describing the socio-political situation during the transition period to the Reform era is considered a sharp social criticism of various problems that hit the country, such as corruption, social inequality, abuse of power, and moral crisis in this study in general aiming to find out how socio-political thinking on Gus Mus's thinking in poetry is studied. In principle, Mustofa Bisri's poem can be used as material in criticizing social and political problems in Indonesia both during the New Order period and today. Based on the study conducted on the poem "The Land of Haha Hihi", it can be seen that the socio-political element is very thick in the poem. The method used is a qualitative method with a review of literary sociology, based on the results of the analysis, it can be concluded that in the analysis there are elements of social and political criticism. The cause of social criticism is the existence of social disparities and social injustice. Meanwhile, the cause of political criticism is power. This is the focus of the author to find social and political criticism in this research.